Nanometer rare earth oxide-containing titanium-based composite powder for 3D printing and preparation method thereof
By using nano rare earth oxide particles and vertical ingot pulling technology in 3D printed titanium-based composites, the problem of difficult control of the enhanced phase size, morphology and distribution of titanium-based composites is solved, and the high strength and toughness of the material and the controllability of the mechanical properties are achieved.
Patent Information
- Application Number
- CN202411811165.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-03-14
AI Technical Summary
In the prior art, the size, morphology and distribution of the reinforced phase of titanium-based composite materials are difficult to control, resulting in uncontrollable mechanical properties of 3D printed titanium-based composite materials.
Nano-rare earth oxide-containing titanium-based composite powder for 3D printing is prepared by vacuum induction magnetic levitation smelting and vertical ingot pulling technology, and nano-rare earth oxide particles are prepared in combination with plasma rotary electrode atomization powder making technology to make them evenly distributed in the titanium-based composite material.
The uniform distribution and stability of nano rare earth oxide particles in titanium-based composite materials are achieved, the coordinated matching of the strength and plasticity of the material is improved, and the uneven distribution of reinforced phases and impurities are avoided due to mechanical ball milling.
Smart Images

Figure CN119614943A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of nonferrous metal processing, in particular to titanium-based composite powder containing nano rare earth oxide for 3D printing, and also to a method for preparing the powder. Background Art
[0002] Titanium and titanium alloys are widely used in aerospace, equipment manufacturing, biomedicine and other fields due to their high specific strength, high specific modulus and good biocompatibility. The introduction of ceramic particles or whiskers as reinforcement phases in titanium alloys can further improve their strength, creep resistance, elastic modulus, etc. However, the size of the in-situ self-generated reinforcement phase is difficult to control, and it is easy to produce stress concentration with the matrix, resulting in a rapid decrease in the plastic toughness of the material, seriously affecting the service safety of the material. Secondly, due to the active chemical properties of titanium, it is extremely susceptible to oxygen contamination, which makes it difficult to melt and process, and the production cost is nearly 30 times that of steel. In addition, traditional subtractive processing will cause more than 90% of material chips to be wasted, and it is difficult to process parts with complex shapes, and the product production cycle is long.
[0003] In recent years, 3D printing has developed rapidly and attracted widespread attention due to its advantages such as high efficiency and energy saving. Thanks to its ultra-high cooling rate (103 K / s-108 K / s), the material structure can be refined and its mechanical properties can be close to the level of forging, providing an effective way to achieve low-cost, high-performance titanium-based composites. However, the raw materials for 3D printed titanium-based composites are currently prepared by mechanically milling spherical titanium powder and external ceramic powder. Mechanical ball milling can induce problems such as powder sphericity destruction, uneven dispersion of ceramic powder, and easy introduction of impurities, resulting in uneven distribution of the reinforcing phase, resulting in uncontrollable mechanical properties of 3D printed titanium-based composites. Summary of the invention
[0004] The purpose of the present invention is to provide a titanium-based composite powder containing nano rare earth oxide for 3D printing, which solves the problem that the size, morphology and distribution of the reinforcement phase of the titanium-based composite material in the prior art are difficult to control.
[0005] The second object of the present invention is to provide a method for preparing titanium-based composite powder containing nano rare earth oxide for 3D printing.
[0006] The first technical solution adopted by the present invention is that the titanium-based composite powder containing nano rare earth oxide for 3D printing is composed of the following components in mass percentage: aluminum 5.0%~7.0%, tin 1.0%~3.0%, zirconium 3.0%~5.0%, molybdenum 0.1%~3.0%, silicon 0.2%~1.0%, rare earth elements 1.0%~3.0%, boron 0.01%~0.05%, and the balance is titanium.
[0007] The present invention is also characterized in that: The rare earth element is any one or a combination of lanthanum, yttrium, cerium, neodymium or gadolinium.
[0008] Boron and zirconium are added in the form of titanium diboride and zirconium hydride respectively, rare earth elements are added in the form of rare earth hydrides, and the remaining elements are added in the form of single substances.
[0009] The second technical solution adopted by the present invention is a method for preparing a titanium-based composite powder containing nano rare earth oxide for 3D printing, and the specific steps are as follows: Step 1: Weigh the raw materials Weigh the following by mass percentage: 5.0% to 7.0% aluminum, 1.0% to 3.0% tin, 3.0% to 5.0% zirconium, 0.1% to 3.0% molybdenum, 0.2% to 1.0% silicon, 1.0% to 3.0% rare earth elements, 0.01% to 0.05% boron, and the balance titanium; Step 2: Ingot smelting The raw materials obtained in step 1 are mixed evenly to obtain a mixed raw material, and the mixed raw material is melted twice using a vacuum induction magnetic levitation melting device to obtain a titanium-based composite material ingot with a diameter of 200 mm; Step 3: Vertically pull the ingot The titanium-based composite material ingot obtained in step 2 is vertically drawn into a titanium-based composite material rod A of φ72 mm×310 mm; Step 4: Rod Preparation The titanium-based composite material rod A obtained in step 3 is machined into a titanium-based composite material rod B of φ70 mm×300 mm; Step 5: Powder preparation The titanium-based composite material rod B obtained in step 4 is prepared into titanium-based composite powder containing nano rare earth oxide using plasma rotating electrode atomization powder making technology.
[0010] The present invention is also characterized in that: The rare earth element is any one or a combination of lanthanum, yttrium, cerium, neodymium or gadolinium.
[0011] Boron and zirconium are added in the form of titanium diboride and zirconium hydride respectively, rare earth elements are added in the form of rare earth hydrides, and the remaining elements are added in the form of single substances.
[0012] The specific process of ingot smelting in step 2 is as follows: the raw materials are mixed evenly and loaded into a water-cooled copper crucible of a vacuum induction magnetic levitation melting equipment, and the vacuum is drawn to 5×10 -4Heating was started after the pressure dropped below Pa, with the initial power set to 200 W. The power was increased by 100 W at an average interval of 2 min to 3 min until the power reached 400 W to 500 W and then kept warm for 8 min to 10 min. The furnace was cooled to room temperature after heating was stopped. The ingot was taken out, turned upside down and placed in a water-cooled copper crucible. The above steps were repeated once to finally obtain a titanium-based composite ingot.
[0013] Step 3 The specific process of vertical ingot pulling is as follows: a φ20 mm × 200 mm round bar is cut from the center line of the titanium-based composite ingot and threaded, and placed in the sealed slot at the bottom of the water-cooled copper crucible as an ingot pulling connecting rod. The remaining titanium-based composite ingot is then placed in the crucible and vacuumed to 5 × 10 -4 Pa or less, and then start heating. The initial power is set to 100W, and the power is increased by 100W every 2min~3min on average until the power reaches 300W~400W, and then keep warm for 8min~10min, then start the ingot pulling transmission system of the vertical ingot pulling equipment, and control the ingot pulling rate at 30mm / min~35mm / min. After the ingot pulling is completed, cool it to room temperature and take it out.
[0014] The discharge port diameter of the vertical ingot pulling equipment is 72mm.
[0015] The titanium-based composite powder containing nano rare earth oxide prepared in step 5 is heat treated in a vacuum tube furnace at a heat treatment temperature of 800° C. and 900° C. for a holding time of 30 min.
[0016] The beneficial effects of the present invention are: (1) The titanium-based composite powder containing nano-rare earth oxides for 3D printing of the present invention is introduced by melt casting-rapid solidification. Thanks to the vertical ingot pulling process, defects such as inclusions and pores in the melt float to the surface of the melt, and the size and distribution of the rare earth oxides in the melt are uniform. In the subsequent rapid solidification process, titanium and rare earth are in the liquid phase, so that nano-scale rare earth oxide particles are uniformly dispersed and precipitated in the composite powder.
[0017] (2) The size, morphology and distribution of the nano-oxide particles in the titanium-based composite powder containing nano-rare earth oxide for 3D printing of the present invention do not change significantly with the increase of heat treatment temperature. The nano-particles hinder dislocation slip while not easily causing large stress concentration, and are expected to achieve a coordinated match between strength and plasticity of the titanium-based composite material.
[0018] (3) The titanium-based composite powder containing nano-rare earth oxide for 3D printing of the present invention can be directly used in the fields of 3D printing or powder metallurgy sintering, avoiding the problems of powder sphericity destruction, uneven distribution of reinforcement phase, introduction of impurities, etc. caused by the mechanical ball milling mixing process, and provides an effective way to prepare high-strength and tough titanium-based composite materials.
[0019] (4) The method for preparing the titanium-based composite powder containing nano-rare earth oxide for 3D printing of the present invention adopts the vertical ingot pulling technology, which makes the defects such as inclusions and pores in the melt float to the surface of the melt by vertical ingot pulling, and makes the size and distribution of the rare earth oxide in the melt uniform. In the subsequent rapid solidification process, titanium and rare earth are in the liquid phase, so that the nano-scale rare earth oxide particles are uniformly dispersed and precipitated in the composite powder. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 It is a schematic flow chart of a method for preparing a titanium-based composite powder containing nano rare earth oxide for 3D printing of the present invention; Figure 2 This is a microstructure diagram of the ingot after vertical pulling during the preparation of the titanium-based composite powder containing nano-rare earth oxides for 3D printing in Example 1 of the present invention; Figure 3 The XRD spectrum of the titanium-based composite powder containing nano rare earth oxide for 3D printing prepared in Example 1 of the present invention; Figure 4 This is a morphology picture of the titanium-based composite powder containing nano rare earth oxide for 3D printing prepared in Example 1 of the present invention; Figure 5 This is a partial enlarged view of the surface of the titanium-based composite powder containing nano rare earth oxide for 3D printing prepared in Example 1 of the present invention; Figure 6a ) is a cross-sectional microstructure diagram of the titanium-based composite powder containing nano rare earth oxide for 3D printing prepared in Example 1 of the present invention; Figure 6b ) is a partial enlarged view of the cross-sectional microstructure diagram of the titanium-based composite powder containing nano rare earth oxide for 3D printing prepared in Example 1 of the present invention; Figure 7 This is a cross-sectional microstructure diagram of the titanium-based composite powder containing nano rare earth oxide for 3D printing prepared in Example 4 after heat treatment at 800° C. and heat preservation for 30 minutes; Figure 8 This is a cross-sectional microstructure diagram of the titanium-based composite powder containing nano rare earth oxide for 3D printing prepared in Example 5 after heat treatment at 900° C. and heat preservation for 30 minutes. DETAILED DESCRIPTION
[0021] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.
[0022] The titanium-based composite powder containing nano-rare earth oxide for 3D printing is composed of the following components in terms of mass percentage: 5.0%~7.0% aluminum, 1.0%~3.0% tin, 3.0%~5.0% zirconium, 0.1%~3.0% molybdenum, 0.2%~1.0% silicon, 1.0%~3.0% rare earth elements, 0.01%~0.05% boron, and the balance is titanium. The rare earth element is any one or a combination of lanthanum, yttrium, cerium, neodymium or gadolinium. Boron and zirconium are added in the form of titanium diboride and zirconium hydride, respectively, and rare earth elements are added in the form of rare earth hydrides, and the remaining elements are added in the form of single substances. The size, morphology and distribution of the nano-oxide particles in the titanium-based composite powder containing nano-rare earth oxide for 3D printing do not change significantly with the increase of heat treatment temperature. Nanoparticles hinder dislocation slip while not easily causing large stress concentration, and are expected to achieve a coordinated match between strength and plasticity of titanium-based composite materials.
[0023] The preparation method of the titanium-based composite powder containing nano rare earth oxide for 3D printing comprises the following specific steps: Step 1: Weigh the raw materials Weigh the following by mass percentage: 5.0% to 7.0% aluminum, 1.0% to 3.0% tin, 3.0% to 5.0% zirconium, 0.1% to 3.0% molybdenum, 0.2% to 1.0% silicon, 1.0% to 3.0% rare earth elements, 0.01% to 0.05% boron, and the balance titanium; The rare earth element is any one or a combination of lanthanum, yttrium, cerium, neodymium or gadolinium. Boron and zirconium are added in the form of titanium diboride and zirconium hydride respectively, the rare earth element is added in the form of rare earth hydride, and the remaining elements are added in the form of single substances.
[0024] Step 2: Ingot smelting The raw materials obtained in step 1 are mixed evenly to obtain a mixed raw material, and the mixed raw material is melted twice using a vacuum induction magnetic levitation melting device to obtain a titanium-based composite material ingot with a diameter of 200 mm; The specific process of ingot smelting is as follows: the raw materials are mixed evenly and loaded into the water-cooled copper crucible of the vacuum induction magnetic levitation melting equipment, and the vacuum is drawn to 5×10 -4 Pa or less, and then heating was started. The initial power was set to 200W, and the power was increased by 100W at an average interval of 2min~3min until the power reached 400W~500W and then kept warm for 8min~10min. After stopping heating, the furnace was cooled to room temperature, the ingot was taken out and turned upside down and placed in a water-cooled copper crucible, and the above steps were repeated once to finally obtain a titanium-based composite ingot.
[0025] Step 3: Vertically pull the ingot The titanium-based composite material ingot obtained in step 2 is vertically drawn into a titanium-based composite material rod A with a diameter of 72 mm and a diameter of 310 mm; The specific process of vertical ingot pulling is as follows: a φ20mm×200mm round bar is cut from the center line of the titanium-based composite ingot and threaded, and placed in the sealed slot at the bottom of the water-cooled copper crucible as an ingot pulling connecting rod. Then the remaining titanium-based composite ingot is put into the crucible and vacuumed to 5×10 -4 Pa or less, and then start heating. The initial power is set to 100W, and the power is increased by 100W every 2min~3min on average until the power reaches 300W~400W, and then keep warm for 8min~10min, then start the ingot pulling transmission system of the vertical ingot pulling equipment, and control the ingot pulling rate at 30mm / min~35mm / min. After the ingot pulling is completed, cool it to room temperature and take it out.
[0026] The discharge port diameter of the vertical ingot pulling equipment is 72mm.
[0027] Step 4: Rod Preparation The titanium-based composite material rod A obtained in step 3 is machined into a titanium-based composite material rod B of φ70 mm×300 mm; Step 5: Powder preparation The titanium-based composite material rod B obtained in step 4 is prepared into a titanium-based composite powder containing nano rare earth oxide by using a plasma rotating electrode atomization powder making device; The titanium-based composite powder containing nano-rare earth oxide obtained in step 5 is heat-treated in a vacuum tube furnace to obtain titanium-based composite powder containing nano-rare earth oxide under different heat treatment conditions.
[0028] The present invention will be further described below by means of specific embodiments: Embodiment 1: Preparation method of titanium-based composite powder containing nano rare earth oxide for 3D printing, the specific process is as follows Figure 1 As shown, follow the steps below to implement: Step 1: Weigh the raw materials Weigh according to mass percentage: aluminum 5.0%, tin 1.0%, zirconium hydride 3.0%, molybdenum 0.1%, silicon 0.2%, lanthanum dihydride 1.0%, titanium diboride 0.01%, titanium 89.69%; Step 2: Ingot smelting The raw materials weighed in step 1 were mixed evenly and loaded into a water-cooled copper crucible of a vacuum induction magnetic levitation melting equipment, and the vacuum was drawn to 5×10 -4 Pa, start heating, set the initial power to 200 W, increase the power by 100 W every 2 min to 3 min on average, keep warm for 8 min to 10 min after the power reaches 400 W to 500 W, stop heating and cool the furnace to room temperature, take out the ingot, turn it upside down and put it into a water-cooled copper crucible, repeat step 2 once, and finally obtain a titanium-based composite ingot with a diameter of 200 mm.
[0029] Step 3: Vertically pull the ingot A φ20 mm × 200 mm round bar was cut from the center line of the titanium-based composite ingot obtained in step 2 and threaded, and placed in the sealed slot at the bottom of the water-cooled copper crucible as an ingot pulling connecting rod. The remaining titanium-based composite ingot was then placed in the crucible and vacuumed to 5 × 10 -4 Pa or less, and then heating was started. The initial power was set to 100W, and the power was increased by 100W at an average interval of 2min~3min until the power reached 300W~400W and then kept warm for 8min~10min. Then the ingot pulling transmission system of the vertical ingot pulling equipment was turned on, and the ingot pulling rate was controlled at 30mm / min~35mm / min. After the ingot pulling was completed and cooled to room temperature, it was taken out to obtain a φ72mm×310 mm titanium-based composite material rod A, and the discharge port diameter of the vertical ingot pulling equipment was 72mm.
[0030] Figure 2 This is the microstructure diagram of the ingot after vertical pulling during the preparation process of the product in this embodiment. Figure 2 It can be seen that the present invention adopts the vertical ingot pulling technology to reduce defects such as inclusions and pores in the melt, and at the same time make the size and distribution of rare earth oxides uniform, and then through rapid solidification, nano-scale rare earth oxide particles are uniformly dispersed and precipitated.
[0031] Step 4: Rod Preparation The rod A obtained in step 3 is machined into a titanium-based composite rod B of φ70 mm×300 mm; Step 5: Powder preparation The rod B obtained in step 4 is prepared into a titanium-based composite powder containing nano rare earth oxide using a plasma rotating electrode atomization powder making device.
[0032] Figure 3 This is the XRD spectrum of the titanium-based composite powder containing nano rare earth oxides prepared in this embodiment. It can be seen from the figure that the prepared titanium-based composite powder containing nano rare earth oxides has diffraction peaks of rare earth oxides and no other impurity peaks, indicating that the prepared titanium-based composite powder containing nano rare earth oxides is relatively pure. Figure 4 This is the morphology picture of the titanium-based composite powder containing nano-rare earth oxide prepared in this embodiment. It can be seen that the titanium-based composite powder containing nano-rare earth oxide prepared by plasma rotating electrode atomization has good sphericity and less powder satellite powder, and is very suitable for the field of additive manufacturing. Figure 5This is a partial enlarged view of the surface of the titanium-based composite powder containing nano-rare earth oxides prepared in this embodiment. It can be seen from the figure that the surface of the prepared titanium-based composite powder containing nano-rare earth oxides is smooth, and only a small amount of white oxide particles are present. This is because the melting point of the oxide is much higher than that of titanium. During the atomization process of the rod material, a small amount of oxide is pushed to the solid-liquid front before being dissolved in the liquid phase and distributed on the powder surface. However, the oxide distribution is small and does not affect the sphericity of the powder, so the effect on the powder fluidity is negligible. Figure 6a ) is a cross-sectional microstructure diagram of the titanium-based composite powder containing nano rare earth oxide prepared in this embodiment, Figure 6b ) is a partial enlarged view of the cross-sectional microstructure diagram of the titanium-based composite powder containing nano-rare earth oxides prepared in this embodiment. It can be seen from the figure that the bright white nano-scale oxide particles in the prepared titanium-based composite powder containing nano-rare earth oxides are evenly dispersed inside the powder, proving that the microstructure of the prepared titanium-based composite powder containing nano-rare earth oxides meets the design requirements.
[0033] Embodiment 2: Preparation method of titanium-based composite powder containing nano rare earth oxide for 3D printing, the specific process is as follows Figure 1 As shown, follow the steps below to implement: Step 1: Weigh the raw materials Titanium-based composite powder containing nano rare earth oxide for 3D printing, weighed according to mass percentage: aluminum 7.0%, tin 3.0%, zirconium hydride 5.0%, molybdenum 3.0%, silicon 1.0%, lanthanum dihydride 3.0%, titanium diboride 0.05%, titanium 77.95%; Step 2: Ingot smelting The raw materials weighed in step 1 were mixed evenly and loaded into a water-cooled copper crucible of a vacuum induction magnetic levitation melting equipment, and the vacuum was drawn to 5×10 -4 Pa or less, and then heating was started. The initial power was set to 200W, and the power was increased by 100W every 2min~3min on average until the power reached 400W~500W, and then the heat was kept for 8min~10min. After the heating was stopped, the furnace was cooled to room temperature. The ingot was taken out and turned upside down and placed in a water-cooled copper crucible. Step 2 was repeated once, and finally a titanium-based composite ingot with a diameter of 200mm was obtained.
[0034] Step 3: Vertically pull the ingot A φ20 mm × 200 mm round bar was cut from the center line of the titanium-based composite ingot obtained in step 2 and threaded, and placed in the sealed slot at the bottom of the water-cooled copper crucible as an ingot pulling connecting rod. The remaining titanium-based composite ingot was then placed in the crucible and vacuumed to 5 × 10 -4Pa, heating was started. The initial power was set to 100W, and the power was increased by 100W every 2min~3min on average until the power reached 300W~400W and then kept warm for 8min~10min. Then the ingot pulling transmission system of the vertical ingot pulling equipment was turned on, and the ingot pulling rate was controlled at 30mm / min~35mm / min. After the ingot pulling was completed and cooled to room temperature, it was taken out to obtain a φ72 mm×310 mm titanium-based composite material rod A. The discharge port diameter of the vertical ingot pulling equipment is 72mm.
[0035] Step 4: Rod Preparation The rod A obtained in step 3 is machined into a titanium-based composite rod B of φ70 mm×300 mm; Step 5: Powder preparation The rod B obtained in step 4 is prepared into a titanium-based composite powder containing nano rare earth oxide using a plasma rotating electrode atomization powder making device.
[0036] Embodiment 3: Preparation method of titanium-based composite powder containing nano rare earth oxide for 3D printing, the specific process is as follows Figure 1 As shown, follow the steps below to implement: Step 1: Weigh the raw materials Weigh according to mass percentage: aluminum 6.0%, tin 2.0%, zirconium hydride 4.0%, molybdenum 2.0%, silicon 0.45%, lanthanum dihydride 1.5%, titanium diboride 0.03%, titanium 84.02%; Step 2: Ingot smelting The raw materials weighed in step 1 were mixed evenly and loaded into a water-cooled copper crucible of a vacuum induction magnetic levitation melting equipment, and the vacuum was drawn to 5×10 -4 Pa or less, and then heating was started. The initial power was set to 200W, and the power was increased by 100W every 2min~3min on average until the power reached 400W~500W, and then the heat was kept for 8min~10min. After the heating was stopped, the furnace was cooled to room temperature. The ingot was taken out and turned upside down and placed in a water-cooled copper crucible. The above steps were repeated once, and finally a titanium-based composite ingot with a diameter of 200mm was obtained.
[0037] Step 3: Vertically pull the ingot A φ20 mm × 200 mm round bar was cut from the center line of the titanium-based composite ingot obtained in step 2 and threaded, and placed in the sealed slot at the bottom of the water-cooled copper crucible as an ingot pulling connecting rod. The remaining titanium-based composite ingot was then placed in the crucible and vacuumed to 5 × 10 -4Pa, heating was started. The initial power was set to 100W, and the power was increased by 100W every 2min~3min on average until the power reached 300W~400W and then kept warm for 8min~10min. Then the ingot pulling transmission system of the vertical ingot pulling equipment was turned on, and the ingot pulling rate was controlled at 30mm / min~35mm / min. After the ingot pulling was completed and cooled to room temperature, it was taken out to obtain a φ72 mm×310 mm titanium-based composite material rod A. The discharge port diameter of the vertical ingot pulling equipment is 72mm.
[0038] Step 4: Rod Preparation The rod A obtained in step 3 is machined into a titanium-based composite rod B of φ70 mm×300 mm; Step 5: Powder preparation The rod material B obtained in step 4 is prepared into a titanium-based composite powder containing nano rare earth oxide by using a plasma rotating electrode atomization powder making device; Embodiment 4: Preparation method of titanium-based composite powder containing nano rare earth oxide for 3D printing, the specific process is as follows Figure 1 As shown, follow the steps below to implement: Step 1: Weigh the raw materials Weigh according to mass percentage: aluminum 6.0%, tin 2.0%, zirconium hydride 4.0%, molybdenum 2.0%, silicon 0.45%, lanthanum dihydride 1.5%, titanium diboride 0.03%, titanium 84.02%; Step 2: Ingot smelting The raw materials weighed in step 1 were mixed evenly and loaded into a water-cooled copper crucible of a vacuum induction magnetic levitation melting equipment, and the vacuum was drawn to 5×10 -4 Pa or less, and then heating was started. The initial power was set to 200W, and the power was increased by 100W every 2min~3min on average until the power reached 400W~500W, and then the heat was kept for 8min~10min. After the heating was stopped, the furnace was cooled to room temperature. The ingot was taken out and turned upside down and placed in a water-cooled copper crucible. The above steps were repeated once, and finally a titanium-based composite ingot with a diameter of 200mm was obtained.
[0039] Step 3: Vertically pull the ingot A φ20 mm × 200 mm round bar was cut from the center line of the titanium-based composite ingot obtained in step 2 and threaded, and placed in the sealed slot at the bottom of the water-cooled copper crucible as an ingot pulling connecting rod. The remaining titanium-based composite ingot was then placed in the crucible and vacuumed to 5 × 10 -4Pa, heating was started. The initial power was set to 100W, and the power was increased by 100W every 2min~3min on average until the power reached 300W~400W and then kept warm for 8min~10min. Then the ingot pulling transmission system of the vertical ingot pulling equipment was turned on, and the ingot pulling rate was controlled at 30mm / min~35mm / min. After the ingot pulling was completed and cooled to room temperature, it was taken out to obtain a φ72 mm×310 mm titanium-based composite material rod A. The discharge port diameter of the vertical ingot pulling equipment is 72mm.
[0040] Step 4: Rod Preparation The rod A obtained in step 3 is machined into a titanium-based composite rod B of φ70 mm×300 mm; Step 5: Powder preparation The rod material B obtained in step 4 is prepared into a titanium-based composite powder containing nano rare earth oxide by using a plasma rotating electrode atomization powder making device; The titanium-based composite powder containing nano-rare earth oxide obtained in step 5 is heat-treated in a vacuum tube furnace to obtain the titanium-based composite powder containing nano-rare earth oxide with a heat treatment temperature of 800° C. and a heat preservation time of 30 minutes. Figure 7 This is a cross-sectional microstructure diagram of the titanium-based composite powder containing nano rare earth oxides prepared in this embodiment after heat treatment. It can be seen from the figure that after the prepared titanium-based composite powder containing nano rare earth oxides is heat treated, the size and morphology of the white nano oxide particles do not change significantly with the increase of the heat treatment temperature, and the powder has good thermal stability.
[0041] Embodiment 5: Preparation method of titanium-based composite powder containing nano rare earth oxide for 3D printing, the specific process is as follows Figure 1 As shown, follow the steps below to implement: Step 1: Weigh the raw materials Weigh according to mass percentage: aluminum 6.0%, tin 2.0%, zirconium hydride 4.0%, molybdenum 2.0%, silicon 0.45%, lanthanum dihydride 1.5%, titanium diboride 0.03%, titanium 84.02%; Step 2: Ingot smelting The raw materials weighed in step 1 were mixed evenly and loaded into a water-cooled copper crucible of a vacuum induction magnetic levitation melting equipment, and the vacuum was drawn to 5×10 -4 Heating was started after the pressure dropped below Pa, with the initial power set to 200 W. The power was increased by 100 W at an average interval of 2 min to 3 min until the power reached 400 W to 500 W and then kept warm for 8 min to 10 min. The furnace was cooled to room temperature after heating was stopped. The ingot was taken out, turned upside down and placed in a water-cooled copper crucible. The above steps were repeated once to finally obtain a titanium-based composite ingot with a diameter of 200 mm.
[0042] Step 3: Vertically pull the ingot A φ20 mm × 200 mm round bar was cut from the center line of the titanium-based composite ingot obtained in step 2 and threaded, and placed in the sealed slot at the bottom of the water-cooled copper crucible as an ingot pulling connecting rod. The remaining titanium-based composite ingot was then placed in the crucible and vacuumed to 5 × 10 -4 Pa, the heating started, the initial power was set to 100W, the power was increased by 100W at an average interval of 2min~3min, and the power was kept warm for 8min~10min after reaching 300W~400W, and then the ingot pulling transmission system of the vertical ingot pulling equipment was turned on, and the ingot pulling rate was controlled at 30mm / min~35mm / min. After the ingot pulling was completed and cooled to room temperature, it was taken out to obtain a φ72 mm×310 mm titanium-based composite material bar A. The discharge port diameter of the vertical ingot pulling equipment is 72mm.
[0043] Step 4: Rod Preparation The rod A obtained in step 3 is machined into a titanium-based composite rod B of φ70 mm×300 mm; Step 5: Powder preparation The rod material B obtained in step 4 is prepared into a titanium-based composite powder containing nano rare earth oxide by using a plasma rotating electrode atomization powder making device; The titanium-based composite powder containing nano-rare earth oxide obtained in step 5 is heat-treated in a vacuum tube furnace to obtain the titanium-based composite powder containing nano-rare earth oxide with a heat treatment temperature of 900° C. and a heat preservation time of 30 minutes. Figure 8 This is a cross-sectional microstructure diagram of the titanium-based composite powder containing nano rare earth oxides prepared in this embodiment after heat treatment. It can be seen from the figure that after the prepared titanium-based composite powder containing nano rare earth oxides is heat treated, the size and morphology of the white nano oxide particles do not change significantly with the increase of the heat treatment temperature, and the powder has good thermal stability.
[0044] Embodiment 6: Preparation method of titanium-based composite powder containing nano rare earth oxide for 3D printing, the specific process is as follows Figure 1 As shown, follow the steps below to implement: Step 1: Weigh the raw materials Weigh according to mass percentage: aluminum 6.0%, tin 2.0%, zirconium hydride 4.0%, molybdenum 2.0%, silicon 0.45%, yttrium hydride 1.5%, titanium diboride 0.03%, titanium 84.02%; Step 2: Ingot smelting The raw materials weighed in step 1 were mixed evenly and loaded into a water-cooled copper crucible of a vacuum induction magnetic levitation melting equipment, and the vacuum was drawn to 5×10 -4Pa or less, and then heating was started. The initial power was set to 200W, and the power was increased by 100W every 2min~3min on average until the power reached 400W~500W, and then the heat was kept for 8min~10min. After the heating was stopped, the furnace was cooled to room temperature. The ingot was taken out and turned upside down and placed in a water-cooled copper crucible. The above steps were repeated once, and finally a titanium-based composite ingot with a diameter of 200mm was obtained.
[0045] Step 3: Vertically pull the ingot A φ20 mm × 200 mm round bar was cut from the center line of the titanium-based composite ingot obtained in step 2 and threaded, and placed in the sealed slot at the bottom of the water-cooled copper crucible as an ingot pulling connecting rod. The remaining titanium-based composite ingot was then placed in the crucible and vacuumed to 5 × 10 -4 Pa, heating was started. The initial power was set to 100W, and the power was increased by 100W every 2min~3min on average until the power reached 300W~400W and then kept warm for 8min~10min. Then the ingot pulling transmission system of the vertical ingot pulling equipment was turned on, and the ingot pulling rate was controlled at 30mm / min~35mm / min. After the ingot pulling was completed and cooled to room temperature, it was taken out to obtain a φ72 mm×310 mm titanium-based composite material rod A. The discharge port diameter of the vertical ingot pulling equipment is 72mm.
[0046] Step 4: Rod Preparation The rod A obtained in step 3 is machined into a titanium-based composite rod B of φ70 mm×300 mm; Step 5: Powder preparation The rod material B obtained in step 4 is prepared into a titanium-based composite powder containing nano rare earth oxide by using a plasma rotating electrode atomization powder making device; The titanium-based composite powder containing nano-rare earth oxide obtained in step 5 is heat-treated in a vacuum tube furnace to obtain the titanium-based composite powder containing nano-rare earth oxide with a heat treatment temperature of 900° C. and a heat preservation time of 30 minutes.
[0047] Embodiment 7: Preparation method of titanium-based composite powder containing nano rare earth oxide for 3D printing, the specific process is as follows Figure 1 As shown, follow the steps below to implement: Step 1: Weigh the raw materials Weigh according to mass percentage: aluminum 6.0%, tin 2.0%, zirconium hydride 4.0%, molybdenum 2.0%, silicon 0.45%, cerium hydride 1.5%, titanium diboride 0.03%, titanium 84.02%; Step 2: Ingot smelting The raw materials weighed in step 1 were mixed evenly and loaded into a water-cooled copper crucible of a vacuum induction magnetic levitation melting equipment, and the vacuum was drawn to 5×10 -4Pa or less, and then heating was started. The initial power was set to 200W, and the power was increased by 100W every 2min~3min on average until the power reached 400W~500W, and then the heat was kept for 8min~10min. After the heating was stopped, the furnace was cooled to room temperature. The ingot was taken out and turned upside down and placed in a water-cooled copper crucible. The above steps were repeated once, and finally a titanium-based composite ingot with a diameter of 200mm was obtained.
[0048] Step 3: Vertically pull the ingot A φ20 mm × 200 mm round bar was cut from the center line of the titanium-based composite ingot obtained in step 2 and threaded, and placed in the sealed slot at the bottom of the water-cooled copper crucible as an ingot pulling connecting rod. The remaining titanium-based composite ingot was then placed in the crucible and vacuumed to 5 × 10 -4 Pa, heating was started. The initial power was set to 100W, and the power was increased by 100W every 2min~3min on average until the power reached 300W~400W and then kept warm for 8min~10min. Then the ingot pulling transmission system of the vertical ingot pulling equipment was turned on, and the ingot pulling rate was controlled at 30mm / min~35mm / min. After the ingot pulling was completed and cooled to room temperature, it was taken out to obtain a φ72 mm×310 mm titanium-based composite material rod A. The discharge port diameter of the vertical ingot pulling equipment is 72mm.
[0049] Step 4: Rod Preparation The rod A obtained in step 3 is machined into a titanium-based composite rod B of φ70 mm×300 mm; Step 5: Powder preparation The rod material B obtained in step 4 is prepared into a titanium-based composite powder containing nano rare earth oxide by using a plasma rotating electrode atomization powder making device; The titanium-based composite powder containing nano-rare earth oxide obtained in step 5 is heat-treated in a vacuum tube furnace to obtain the titanium-based composite powder containing nano-rare earth oxide with a heat treatment temperature of 900° C. and a heat preservation time of 30 minutes.
[0050] Embodiment 8: Preparation method of titanium-based composite powder containing nano rare earth oxide for 3D printing, the specific process is as follows Figure 1 As shown, follow the steps below to implement: Step 1: Weigh the raw materials Weigh according to mass percentage: aluminum 6.0%, tin 2.0%, zirconium hydride 4.0%, molybdenum 2.0%, silicon 0.45%, neodymium hydride 1.5%, titanium diboride 0.03%, titanium 84.02%; Step 2: Ingot smelting The raw materials weighed in step 1 were mixed evenly and loaded into a water-cooled copper crucible of a vacuum induction magnetic levitation melting equipment, and the vacuum was drawn to 5×10 -4Pa or less, and then heating was started. The initial power was set to 200W, and the power was increased by 100W every 2min~3min on average until the power reached 400W~500W, and then the heat was kept for 8min~10min. After the heating was stopped, the furnace was cooled to room temperature. The ingot was taken out and turned upside down and placed in a water-cooled copper crucible. The above steps were repeated once, and finally a titanium-based composite ingot with a diameter of 200mm was obtained.
[0051] Step 3: Vertically pull the ingot A φ20 mm × 200 mm round bar was cut from the center line of the titanium-based composite ingot obtained in step 2 and threaded, and placed in the sealed slot at the bottom of the water-cooled copper crucible as an ingot pulling connecting rod. The remaining titanium-based composite ingot was then placed in the crucible and vacuumed to 5 × 10 -4 Pa, heating was started. The initial power was set to 100W, and the power was increased by 100W every 2min~3min on average until the power reached 300W~400W and then kept warm for 8min~10min. Then the ingot pulling transmission system of the vertical ingot pulling equipment was turned on, and the ingot pulling rate was controlled at 30mm / min~35mm / min. After the ingot pulling was completed and cooled to room temperature, it was taken out to obtain a φ72 mm×310 mm titanium-based composite material rod A. The discharge port diameter of the vertical ingot pulling equipment is 72mm.
[0052] Step 4: Rod Preparation The rod A obtained in step 3 is machined into a titanium-based composite rod B of φ70 mm×300 mm; Step 5: Powder preparation The rod material B obtained in step 4 is prepared into a titanium-based composite powder containing nano rare earth oxide by using a plasma rotating electrode atomization powder making device; The titanium-based composite powder containing nano-rare earth oxide obtained in step 5 is heat-treated in a vacuum tube furnace to obtain the titanium-based composite powder containing nano-rare earth oxide with a heat treatment temperature of 900° C. and a heat preservation time of 30 minutes.
[0053] Embodiment 9: Preparation method of titanium-based composite powder containing nano rare earth oxide for 3D printing, the specific process is as follows Figure 1 As shown, follow the steps below to implement: Step 1: Weigh the raw materials Weigh according to mass percentage: aluminum 6.0%, tin 2.0%, zirconium hydride 4.0%, molybdenum 2.0%, silicon 0.45%, gadolinium hydride 1.5%, titanium diboride 0.03%, titanium 84.02%; Step 2: Ingot smelting The raw materials weighed in step 1 were mixed evenly and loaded into a water-cooled copper crucible of a vacuum induction magnetic levitation melting equipment, and the vacuum was drawn to 5×10 -4Pa or less, and then heating was started. The initial power was set to 200W, and the power was increased by 100W every 2min~3min on average until the power reached 400W~500W, and then the heat was kept for 8min~10min. After the heating was stopped, the furnace was cooled to room temperature. The ingot was taken out and turned upside down and placed in a water-cooled copper crucible. The above steps were repeated once, and finally a titanium-based composite ingot with a diameter of 200mm was obtained.
[0054] Step 3: Vertically pull the ingot A φ20 mm × 200 mm round bar was cut from the center line of the titanium-based composite ingot obtained in step 2 and threaded, and placed in the sealed slot at the bottom of the water-cooled copper crucible as an ingot pulling connecting rod. The remaining titanium-based composite ingot was then placed in the crucible and vacuumed to 5 × 10 -4 Pa, heating was started. The initial power was set to 100W, and the power was increased by 100W every 2min~3min on average until the power reached 300W~400W and then kept warm for 8min~10min. Then the ingot pulling transmission system of the vertical ingot pulling equipment was turned on, and the ingot pulling rate was controlled at 30mm / min~35mm / min. After the ingot pulling was completed and cooled to room temperature, it was taken out to obtain a φ72 mm×310 mm titanium-based composite material rod A. The discharge port diameter of the vertical ingot pulling equipment is 72mm.
[0055] Step 4: Rod Preparation The rod A obtained in step 3 is machined into a titanium-based composite rod B of φ70 mm×300 mm; Step 5: Powder preparation The rod material B obtained in step 4 is prepared into a titanium-based composite powder containing nano rare earth oxide by using a plasma rotating electrode atomization powder making device; The titanium-based composite powder containing nano-rare earth oxide obtained in step 5 is heat-treated in a vacuum tube furnace to obtain the titanium-based composite powder containing nano-rare earth oxide with a heat treatment temperature of 900° C. and a heat preservation time of 30 minutes.
Claims
1. Titanium-based composite powder containing nano rare earth oxide for 3D printing, characterized in that: The composition is as follows in terms of mass percentage: aluminum 5.0%~7.0%, tin 1.0%~3.0%, zirconium 3.0%~5.0%, molybdenum 0.1%~3.0%, silicon 0.2%~1.0%, rare earth elements 1.0%~3.0%, boron 0.01%~0.05%, and the balance is titanium.
2. The titanium-based composite powder containing nano rare earth oxide for 3D printing according to claim 1, characterized in that: The rare earth element is any one or a combination of lanthanum, yttrium, cerium, neodymium or gadolinium.
3. The titanium-based composite powder containing nano rare earth oxide for 3D printing according to claim 1, characterized in that: The boron element and the zirconium element are added in the form of titanium diboride and zirconium hydride respectively, the rare earth element is added in the form of rare earth hydride, and the remaining elements are added in the form of single substances.
4. A method for preparing a titanium-based composite powder containing nano rare earth oxide for 3D printing, characterized in that: The specific steps are as follows: Step 1: Weigh the raw materials Weigh the following by mass percentage: 5.0% to 7.0% aluminum, 1.0% to 3.0% tin, 3.0% to 5.0% zirconium, 0.1% to 3.0% molybdenum, 0.2% to 1.0% silicon, 1.0% to 3.0% rare earth elements, 0.01% to 0.05% boron, and the balance titanium; Step 2: Ingot smelting The raw materials obtained in step 1 are mixed evenly to obtain a mixed raw material, and the mixed raw material is melted twice using a vacuum induction magnetic levitation melting device to obtain a titanium-based composite material ingot with a diameter of 200 mm; Step 3: Vertically pull the ingot The titanium-based composite material ingot obtained in step 2 is vertically drawn into a titanium-based composite material rod A of φ72 mm×310 mm; Step 4: Rod Preparation The titanium-based composite material rod A obtained in step 3 is machined into a titanium-based composite material rod B of φ70 mm×300 mm; Step 5: Powder preparation The titanium-based composite material rod B obtained in step 4 is prepared into a titanium-based composite powder containing nano rare earth oxide using a plasma rotating electrode atomization powder making device.
5. The method for preparing the titanium-based composite powder containing nano rare earth oxide for 3D printing according to claim 4, characterized in that: The rare earth element is any one or a combination of lanthanum, yttrium, cerium, neodymium or gadolinium.
6. The method for preparing the titanium-based composite powder containing nano rare earth oxide for 3D printing according to claim 4, characterized in that: The boron element and the zirconium element are added in the form of titanium diboride and zirconium hydride respectively, the rare earth element is added in the form of rare earth hydride, and the remaining elements are added in the form of single substances.
7. The method for preparing the titanium-based composite powder containing nano rare earth oxide for 3D printing according to claim 4, characterized in that: The specific process of ingot smelting in step 2 is as follows: The raw materials were mixed evenly and loaded into a water-cooled copper crucible of a vacuum induction magnetic levitation melting equipment. The vacuum was drawn to 5×10 -4 Pa; the initial power is set to 200 W, and the power is increased by 100 W every 2 min to 3 min on average until the power reaches 400 W to 500 W and then kept warm for 8 min to 10 min. After the heating is stopped, the furnace is cooled to room temperature; the ingot is taken out and turned upside down and placed in a water-cooled copper crucible, and the above steps are repeated once to finally obtain a titanium-based composite material ingot.
8. The method for preparing the titanium-based composite powder containing nano rare earth oxide for 3D printing according to claim 4, characterized in that: The specific process of vertical ingot pulling in step 3 is as follows: a round bar of φ20 mm×200 mm is cut from the center line of the titanium-based composite material ingot and threaded, and placed in the sealed card slot at the bottom of the water-cooled copper crucible as an ingot pulling connecting rod, and then the remaining titanium-based composite material ingot is put into the crucible and vacuumed to 5×10 -4 Heating starts after the temperature drops below Pa, with the initial power set to 100 W. The power is increased by 100 W every 2 min to 3 min on average until the power reaches 300 W to 400 W, then the power is kept warm for 8 min to 10 min. Subsequently, the ingot pulling transmission system of the vertical ingot pulling equipment is turned on, and the ingot pulling rate is controlled at 30 mm / min to 35 mm / min. After the ingot pulling is completed, it is taken out after cooling to room temperature.
9. The method for preparing the titanium-based composite powder containing nano rare earth oxide for 3D printing according to claim 8, characterized in that: The diameter of the discharge port of the vertical ingot pulling equipment is 72 mm.
10. The method for preparing the titanium-based composite powder containing nano rare earth oxide for 3D printing according to claim 9, characterized in that: The titanium-based composite powder containing nano rare earth oxide prepared in step 5 is heat treated in a vacuum tube furnace at a heat treatment temperature of 800° C. and 900° C. for a holding time of 30 min.
Citation Information
Cited By
Rare earth synergistic refining high-toughness aluminum-lithium alloy component optimization method for additive manufacturing
CN122164895A
Composition optimization method of high strength and toughness aluminum lithium alloy for additive manufacturing with rare earth synergistic refinement
CN122164895B